The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/aerospace8030074
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Research in Subscale Flight Testing and Analysis of Its Main Practical Challenges

Abstract: Testing of untethered subscale models, often referred to as subscale flight testing, has traditionally had a relatively minor, yet relevant use in aeronautical research and development. As recent advances in electronics, rapid prototyping and unmanned-vehicle technologies expand its capabilities and lower its cost, this experimental method is seeing growing interest across academia and the industry. However, subscale models cannot meet all similarity conditions required for simulating full-scale flight. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…3 it is possible to see the layers that composethe Neuro-Fuzzy architecture. REVISTA OBSERVATORIO DE LA ECONOMIA LATINOAMERICANA Curitiba, v.22, n.1, p. 1898-1919. 2024.…”
Section: Neuro-fuzzymentioning
confidence: 99%
“…3 it is possible to see the layers that composethe Neuro-Fuzzy architecture. REVISTA OBSERVATORIO DE LA ECONOMIA LATINOAMERICANA Curitiba, v.22, n.1, p. 1898-1919. 2024.…”
Section: Neuro-fuzzymentioning
confidence: 99%
“…However, in the case of UAV development, developers, especially researchers, often use existing COTS airframes that have limited parameters available. A review by Sobron et al of research platforms between 2010 and 2020 showed that at least 18 of the aircraft surveyed were developed from COTS airframes [81]. Beyond the scope of the aforementioned review, commercial (closed-design) airframes such as the UAV Factory Penguin airframe have been used as a basis by over 20 research institutions since 2010 with similarly limited parameters available [82].…”
Section: Measurementmentioning
confidence: 99%
“…There have also been studies of UAV performance through stall or upset maneuvers [11][12][13][14]. In addition, new aircraft configurations [15][16][17][18] and flight control hardware and software [19][20][21][22][23] have been tested. Research evaluating aircraft power consumption reduction through steady and dynamic soaring has also become the subject of significant attention recently [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent UAV flight test campaigns include [89][90][91][92][93][94][95][96][97][98][99], which also include flight testing with incremental type control laws in [100][101][102][103][104]. Subscale flight testing and system identification was performed in [105][106][107][108][109]. In [110], both system identification and control law design were performed for the longitudinal motion of a fixed wing UAV.…”
Section: Introductionmentioning
confidence: 99%